Living with an implantable cardiac device - Przemysław Sawicki; Piotr Małyszka; Łukasz Wołowiec; Bartosz Górny; Małgorzata Chudzińska; Walery Zukow; Władysław Sinkiewicz (Kazimierz Wielki University, 2017)
The number of patients with implantable cardiac devices (CIEDs) is rapidly increasing. One of the reason behind this phenomenon is aging population and sophisticated treatment of coronary artery disease but also new technologies are continually evolving. Indication for the implantation are changing following new trials results proving the reduction of  mortality and morbidity rates. With the technological development that is currently taking place, there is a growing number of electromagnetic signals which can potentially create electromagnetic interference (EMI)  with cardiac devices.  This study aims to bring closer the matter of living with cardiac device to all kind of medical staff and patients, with special regard to potential sources of electromagnetic interference and its effect on cardiac devices. The paper also updates contraindications and optimize management in a variety of "real life" situations.